Academic Information Security Researchers: Hackers or Specialists? - Dadkhah, Mehdi; Lagzian, Mohammad; Borchardt, Glenn (Science & Engineering Ethics, 2018)
In this opinion piece, we present a synopsis of our findings from the last 2 years concerning cyber-attacks on web-based academia. We also present some of problems that we have faced and try to resolve any misunderstandings about our work. We are academic information security specialists, not hackers. Finally, we present a brief overview of our methods for detecting cyber fraud in an attempt to present general guidelines for researchers who would like to continue our work. We believe that our work is necessary for protecting the integrity of scholarly publishing against emerging cybercrime.